ГЛЯЦИОГЕННЫЕ ДЕФОРМАЦИИ ЗОЛОТА ИЗ ПСЕФИТОВ СЫСОЛЬСКОЙ МУЛЬДЫ - Глухов Ю.В.; Филиппов В.Н.; Исаенко С.И.; Макеев Б.А.; Терентьев А.В.; Бушенев В.Н.; Патова В.А. (My University, 2006)
The paper displays new data on morphology and composition of gold in the Middle Jurassic paleo-placer occurrence named Bezdubovo (in Sysolskaya syncline, Komi republic). Gold particles and associated minerals were studied with the scanning electron microscope JSM-6400 with energy spectrometer Link ISIS-300. The whole selection included 139 gold particles extracted from three samples (total volume 0.03 m3). The particles range in size from 0.04 to 0.43 mm, but fine (0.1-0.25 mm) and the finest (0.05-0.1 mm) classes make the dominant part of the whole scope (97 %). Practically all gold (99 %) is represented by plated flake-like particles with extremely high fineness of the superficial metal - 1000 %o Au. Thickness of gold flakes varies from 0.005 to 0.05 mm, but mostly (87 %) it is within the narrow range from 0.01 to 0.02 mm. Concentrations of gold in the Middle Jurassic pscphites (as estimated by three samples with individual volumes 0.01 m3) vary from 0.31 to 0.57 mg/0.01 m3. Morphology of the studied palcoplacer gold is characterized by numerous and variable non-crystalline coarse-angulated forms of secondary deformations (pressing forms), together with remaining signs of rounded shapes typical for particles treated in water streams and wind activity. The origin of widespread «press-forms» can be explained by strong one-event pressing of unconsolidated gold-bearing sediments, which is probably caused by Pleistocene glacial movements.
Keywords: Мезозой::Юрская; Кайнозой::Четвертичная::Плейстоцен